2017
DOI: 10.1111/php.12750
|View full text |Cite
|
Sign up to set email alerts
|

Light‐Induced Conformational Changes in the Plant Cryptochrome Photolyase Homology Region Resolved by Selective Isotope Labeling and Infrared Spectroscopy

Abstract: Plant cryptochromes are photoreceptors that regulate flowering, circadian rhythm and photomorphogenesis in response to blue and UV-A light. It has been demonstrated that the oxidized flavin cofactor is photoreduced to the neutral radical state via separate electron and proton transfer. Conformational changes have been found in the C-terminal extension, but few studies have addressed the changes in secondary structure in the sensory photolyase homology region (PHR). Here, we investigated the PHR of the plant cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 47 publications
(83 reference statements)
2
18
0
2
Order By: Relevance
“…5C). Fourier transform infrared experiments on plant CRY showed that the intermediate state for signaling has marked loss of -sheet structure in the PHR domain upon illumination (35,36). The same trend is found in dCRY in the present study.…”
Section: Helix-to-coil Transition Of the Ctt Is Coupled To The Overall Protein Fluctuationssupporting
confidence: 86%
“…5C). Fourier transform infrared experiments on plant CRY showed that the intermediate state for signaling has marked loss of -sheet structure in the PHR domain upon illumination (35,36). The same trend is found in dCRY in the present study.…”
Section: Helix-to-coil Transition Of the Ctt Is Coupled To The Overall Protein Fluctuationssupporting
confidence: 86%
“…Thus, the mechanism coupling FAD reduction to the CTT may differ. Notably, in AtCRY1, photoactivation leads to conformational changes with the αβ domain that has not been observed in other CRYs 73,77,112 . It is intriguing to postulate that such changes may lead to reorganization of the secondary pocket to alter CTT interactions at this site in a manner analogous to light‐independent regulation of Type II CRY:CLOCK interactions.…”
Section: Ctt Dynamics In Other Photoactive Cry Lineagesmentioning
confidence: 97%
“…Notably, in AtCRY1, photoactivation leads to conformational changes with the αβ domain that has not been observed in other CRYs. 73,77,112 It is intriguing to postulate that such changes may lead to reorganization of the secondary pocket to alter CTT interactions at this site in a manner analogous to light-independent regulation of Type II CRY:CLOCK interactions. Second, Type IV CRYs can access the FADH À state, which will also lead to introduction of negative charge.…”
Section: Ctt Dynamics In Other Photoactive Cry Lineagesmentioning
confidence: 99%
“…Generally, photoreceptor activation occurs well under a second, making it fast compared to many cellular events (excepting the millisecond and faster time scale processes common in the neurosciences). For example, the detachment and unfolding of Jα in As LOV2 is complete within 0.3–1.0 ms. Comparable structural perturbations in associating photoreceptor systems are equally fast, occurring on the submillisecond time scale in plant cryptochromes. Similarly, the photodissociation of multimeric BLUF proteins takes place within 4 to 45 ms, and the light-induced dimerization of Neurospora crassa Vivid ( Nc Vivid) is complete within 20 ms, compatible with a diffusion-limited process under the conditions tested . As such, aspects other than the inherent photochemical mechanisms typically limit the on-kinetics with which an optogenetic response can be triggered.…”
Section: Photoreceptor Engineeringmentioning
confidence: 99%